Quantifying the movement characteristics of Australian Football League women's competition - Thornton, H. R.; Armstrong, C. R.; Gamble, T.; Rigby, A.; Johnston, R. D.; Duthie, G. M. (The Journal of Strength and Conditioning Research, 2022)
The purpose is to provide an overview of the externally measured movement characteristics of Australian Football League Women's (AFLW) competition, and the variability in this between matches. A range of movement variables were measured from 28 athletes who wore 10-Hz global positioning system devices during games and were summarized according to positional groups. The variance in each athlete's match loads for each round were expressed using standardized scores (z-scores), and the change compared with the first game played was calculated and expressed as a standard deviation. Furthermore, using the raw export, moving means (1-10 minutes) of speed (m/min) and acceleration (m/s) were calculated. Following log transformation of the maximal means, intercept and slopes were calculated. Linear mixed models identified differences between positional groups for match loads, and intercept and slopes. Effects were described using standardized effect sizes (ESs) and magnitude-based decisions. There were no substantial and unclear differences between positional groups for match loads (ES range; ±confidence limits = 0.10-0.80; ±0.30-4.30) and for intercept and slopes (ES range; 0.04-0.44; ±0.52-2.11). Large within-athlete variation in match demands between rounds was observed (z-score up to -1.8 SD for distance), and the maximal means for speed and acceleration demonstrate the extensive physical demands of AFLW competition. These data describe the intense and variable physical demands of AFLW competition, and further provide novel information regarding the maximal mean intensities and intercept and slopes, which should assist practitioners in planning and prescribing training in preparation for competition.